Mutated β-catenin evades a microRNA-dependent regulatory loop - Veronese, Angelo (National Academy of Sciences, 2011)
hsa-mir-483 is located within intron 2 of the IGF2 gene. We have previously shown oncogenic features of miR-483-3p through cooperation with IGF2 or by independently targeting the proapoptotic gene BBC3/PUMA. Here we demonstrate that expression of miR-483 can be induced independently of IGF2 by the oncoprotein β-catenin through an interaction with the basic helix–loop–helix protein upstream stimulatory transcription factor 1. We also show that β-catenin itself is a target of miR-483-3p, triggering a negative regulatory loop that becomes ineffective in cells harboring an activating mutation of β-catenin. These results provide insights into the complex regulation of the IGF2/miR-483 locus, revealing players in the β-catenin pathway.